THE EFFECT OF AL-THARTHAR –EUPHRATES CANAL ON THE SOME ECOLOLOGICAL PROPERTIES OF EUPHRATES RIVER - Al-Dhamin, Ahmed; Mahmood, Mahmood; Rabee, Adel; Fadhel, Laith (Iraqi Journal of Science, 2024)
The present study was designed for two targets , the first, to demonstrate the seasonal variations in physic-chemical parameters of Al-Tharthar-Euphrates canal and River Euphrates and the second is explain the possible effects of canal on some ecological properties in Euphrates river. Water samples were collected seasonally from both sides for a period of spring (April) 2009 to winter (February) 2010. Twenty two parameters were studied included temperature, pH, dissolved oxygen, biological oxygen demand, electrical conductivity , total dissolved solids, total hardness, alkalinity, total suspended solids, calcium, magnesium, potassium, sodium, chloride, nitrate, phosphate, lead, manganese, copper, nickel, iron and zinc.These parameters were compared with water quality standards to evaluate the quality of water in canal and river for public usage. The almost water quality parameters remained within the safe limits through the study period except total hardness, chloride, calcium manganese, copper, lead and nickel were recorded concentrations in some seasons higher than the permissible limits values for drinking water. The results also showed that the Al-Tharthar-Euphrates canal contributes in significant increase for the total hardness values and significant decrease of EC , TDS, TSS, K, Na, Cl and NO3 in Euphrates river.